Testing the effect of ecolabels on the environmental impact of food purchases in worksite cafeterias: a randomised controlled trial - Madison Luick; Cristina Stewart; Michael Clark; Paul Bateman; Elizabeth Biggs; Brian Cook; Melissa Little; Gina M. Wren; Susan A. Jebb; Rachel Pechey (BMC Public Health)
Abstract Background Reducing the environmental impact of foods consumed is important for meeting climate goals. We aimed to conduct a randomised controlled trial to test whether ecolabels reduce the environmental impact of food selected in worksite cafeterias, alone or in combination with increased availability of more sustainable meal options. Methods Worksite cafeterias (n = 96) were randomised to one of three study groups, with 54 included for final analysis. One group was intended to increase the availability of meat-free options, but no change was implemented. Therefore, this group was treated as part of the control, creating two groups: (1) control (no ecolabels) (n = 35), and (2) ecolabels (n = 19). Regression analysis assessed the primary outcome of total environmental impact of hot meals sold over a 6-week period. Secondary outcome analyses explored the individual environmental indicators that composed the total environmental impact score (i.e., greenhouse gas emissions, biodiversity loss, eutrophication, and water scarcity). The mean weekly environmental impact scores of hot meal options over the full 12-week trial period were assessed using hierarchical mixed effects models. Results There was no significant effect of the intervention on the environmental impact scores of meals sold (mean difference between control and intervention sites: -1.4%, 95%CI: -33.6%, + 30.8%). There was no evidence of an effect in mean weekly environmental impact score (-5.4%, 95%CI: -12.6%, + 2.5%), nor in any of the four individual environmental indicators (greenhouse gas emissions: -3.6%, 95%CI: -30.7%, 34.3%; biodiversity loss: 2.0%, 95%CI: -25.8%, 40.2%; eutrophication: -2.4%, 95%CI: -29.3%, 34.7%; water scarcity: -0.4%, 95%CI: -28.7%, 39.1%). Conclusions Ecolabels may not be an effective tool to shift consumer behaviour in worksite cafeterias towards meals with lower environmental impact. Trial registration The study was pre-registered prospectively on ISRCTN ( https://www.isrctn.com/ISRCTN10268258 ; 06/01/2022).